2016
DOI: 10.3847/0004-637x/820/1/11
|View full text |Cite
|
Sign up to set email alerts
|

CONFIRMING THE EXISTENCE OF A QUIESCENT GALAXY POPULATION OUT TO z = 3: A STACKING ANALYSIS OF MID-, FAR-INFRARED, AND RADIO DATA

Abstract: We performed a comprehensive stacking analysis on ∼14,200 quiescent galaxy (QG) candidates at z=0-3 across mid-, far-infrared (MIR and FIR), and radio wavelengths. Identified via their rest-frame NUV−r and r−J colors, the QG candidates (M M 10 9.8 12.2 - =  ) have drastically different IR and radio properties depending on their 24 μm emission strength. The fraction of QG candidates with strong 24 μm emission (equivalent to inferred star formation rates SFR M yr 100, hereafter "IR-bright") increases wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 68 publications
3
17
1
Order By: Relevance
“…Afterwards, the SFR is quenched by feedbacks and the galaxy will then evolve passively to become a local early-type; then it will populate a region of the SFR versus stellar mass diagram substantially below the main sequence. These loci of 'red and dead' galaxies are indeed observed locally (see Renzini & Peng 2015), and start to be pinpointed even at high redshift (see Man et al 2016). …”
Section: Resultsmentioning
confidence: 97%
“…Afterwards, the SFR is quenched by feedbacks and the galaxy will then evolve passively to become a local early-type; then it will populate a region of the SFR versus stellar mass diagram substantially below the main sequence. These loci of 'red and dead' galaxies are indeed observed locally (see Renzini & Peng 2015), and start to be pinpointed even at high redshift (see Man et al 2016). …”
Section: Resultsmentioning
confidence: 97%
“…Several authors have noted that the IR luminosity (or observed-frame 24 µm luminosity, generally the only available tracer of dust emission at low SFR and high redshift) can overestimate the obscured SFR of quiescent galaxies, in some cases quite severely (e.g., Salim et al 2009;Hayward et al 2014;Utomo et al 2014;Man et al 2016). This can be due to several effects, including the fact that the IR luminosity is a long-lived tracer compared to the instantaneous SFR, and 24 µm emission can be boosted by dust heating unrelated to star formation, including circumstellar dust heated by intermediate-age AGB stars, extended cirrus dust heated by old stellar populations, or weak nuclear activity.…”
Section: Sfr Estimationmentioning
confidence: 99%
“…In practice, passive sources that might be discarded in this way amount only to a small fraction (of order 10%-15%) of the total. This classification as passive is not always fully reliable, and in some cases galaxies classified as such might actually have positive IR emission (Man et al 2016;Gobat et al 2017). By discarding passive galaxy candidates, we could erroneously miss some genuine FIR-emitting galaxies in trade for a fairly small benefit.…”
Section: Setting the General Prior Source Listmentioning
confidence: 99%